Chronic gastrite: modern state of the problem - O. N. Minushkin (Терапевтический архив, 2020)
Aim. Тo evaluate the modern view on the problem of chronic gastritis and the effectiveness of the drug ursodexic acid (UHC) Grinterol in the treatment of patients with chronic antral reflux-gastritis (biliar).